The Relationship between Knowledge and the Occurrence of Vaginal Discharge - Dian Purbasari; Suesti; Intan Mutiara Putri; Gokir Nengak (The Indonesian Institute of Science and Technology Research, 2023)
This study aimed to investigate the relationship between knowledge of vulva hygiene and the occurrence of vaginal discharge among female students in the female boarding high school in Indonesia. A total of 48 students were selected through purposive sampling and data was collected using a questionnaire. The results showed that 31.8% of unmarried women or adolescent girls aged 12-24 years experienced vaginal discharge. Lack of knowledge about vaginal discharge among adolescents and feeling embarrassed to consult health professionals were the reasons for not seeking treatment. This puts adolescent girls at a higher risk of experiencing vaginal discharge. The analysis using the Chi-square test showed a significant relationship (p<0.05) between knowledge of vulva hygiene and the occurrence of vaginal discharge, with a correlation coefficient of 0.416, indicating a moderate relationship. Therefore, it is recommended that respondents increase their knowledge of vulva hygiene, and those experiencing pathological vaginal discharge should improve genital hygiene to avoid future health issues.